The Probe Team [episode no. 307] - Patinio, Joe (Probe Productions, 1994)
Here they go again is about the Mt. Pinatubo lahar victims in their resettlement area in Tarlac. Chorela is discussed in the second part. Signature Art is an interview with Joe Patinio.